The Role of Indonesian School’s Instructional Leadership in Malaysia - Lani, Ahmad; Pauzi, Hezzrin Mohd (ALEXANDRIA (Journal of Economics, Business, & Entrepreneurship), 2024)
The existence of Indonesian school in Malaysia has a significant contribution in providing the education of Indonesian children. The schools were formed with the aim in protecting the Indonesian children’s right to the access of the formal education. This is in accordance with the mandate of 1945’s constitution since the establishment of Indonesia, which requires every of its citizens have good access to the formal education. Indonesian school basically have two bases particularly the Indonesian school of Kuala Lumpur (SIKL) as education base in Peninsular Malaysia, and Indonesian school of Kota Kinabalu (SIKK) as the education center for Indonesian children who living in Sabah and Sarawak. Instructional programs adopted based on the education system implemented in Indonesia, which comprise of curriculum and extracurricular programs. This study used qualitative research in order to obtain a comprehensive picture of the Indonesian school’s instructional leadership. The purpose of this paper is to determine the role of Indonesian school in shaping the student’s character. Interview has been conducted to 11 participants of the school principals and teachers. The findings show that instructional leadership of Indonesian school fundamentally promoting the student’s achievement and character development in nationalism, religion, and social interest through imposing the curriculum and extracurricular program included implementing the Pancasila character education at the school. This study suggests that the school’s stakeholders including parent’s involvement need to participate closely in supporting and facilitating the student’s necessity in developing their character and enhancing the achievement as future provision of the young generation.